1991
DOI: 10.1007/bf00400280
|View full text |Cite
|
Sign up to set email alerts
|

Impaired response to angiotensin II in Type 1 (insulin-dependent) diabetes mellitus. Role of prostaglandins and sodium-lithium countertransport activity

Abstract: The pathogenesis of diabetic nephropathy remains elusive. A role for renal prostaglandins in antagonizing the hormonal effects of renin-angiotensin II has been postulated as a putative factor leading to hyperfiltration in patients with Type 1 (insulin-dependent) diabetes mellitus. Our aim was to elucidate the effects of angiotensin II on kidney haemodynamics and on blood pressure in eight normal subjects, in nine normotensive, in nine hypertensive with normal sodium-lithium countertransport activity in erythro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…Our observations made 7-10 days after induction of diabetes agree with the conclusion of Sarubbi and colleagues (31) that a substantial decline in renal reactivity occurs between 5 and 14 days of streptozotocin-induced diabetes. A diminished renal arteriolar response to Ang I1 also corroborates other studies of human (15) and experimental diabetes (29,37); like these results from hydronephrotic kidneys (Fig. l) First, a reduced glomerular receptor density (2,38), if also applicable to the microvessels, would lead to a reduced arteriolar constrictor response.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our observations made 7-10 days after induction of diabetes agree with the conclusion of Sarubbi and colleagues (31) that a substantial decline in renal reactivity occurs between 5 and 14 days of streptozotocin-induced diabetes. A diminished renal arteriolar response to Ang I1 also corroborates other studies of human (15) and experimental diabetes (29,37); like these results from hydronephrotic kidneys (Fig. l) First, a reduced glomerular receptor density (2,38), if also applicable to the microvessels, would lead to a reduced arteriolar constrictor response.…”
Section: Discussionsupporting
confidence: 88%
“…The numerous mechanisms that may account for the low resistance of renal microvessels in diabetes include alterations in the renin-angiotensin system (1, 3 , 19). Evidence that human (15) and experimental (29,31) diabetic subjects exhibit an impaired renal vascular response to angiotensin I1 (Ang 11) led to speculation that a diminished constrictor response could contribute to the loss of blood flow control (18,20,27,40). Overproduction of vasodilator prostaglandins in diabetic kidneys (13,14,26,32) suggested that prostaglandins might also play a role in the hyperfiltration via direct arteriolar dilation and/or attenuation of vascular responsiveness to Ang 11.…”
Section: Introductionmentioning
confidence: 99%
“…The renal synthesis of prostaglandins is frequently increased in subjects with short-term insulin-dependent diabetes mellitus (IDDM) (9, 43) making them less susceptible to infusions of vasoconstrictor agents (8).…”
Section: Discussionmentioning
confidence: 99%
“…The changes in baseline CBV after ASA, however, should be interpreted with caution, due to the small sample sizes and wide variation in data. In short-term diabetes, renal hyperperfusion and hyperfiltration are partly due to elevated prostacyclin production [13,34,35]. We demonstrated previously that inhibition of prostaglandin synthesis reduces hyperfiltration [36].…”
Section: Discussionmentioning
confidence: 99%